Loch Leven Waterfowl 1968-2007 ... - Mitchell, N; Brooks, P.; Squire, J.; Wright, G.; Allison, A. (NERC Environmental Information Data Centre, 2015)
The dataset comprises counts of ten waterfowl species collected from Loch Leven from 1968-2007 by staff at Scottish Natural Heritage (SNH) and its predecessor bodies (Nature Conservancy), as part of their long-term monitoring programme of the lake. Counts are for the whole loch and represent an annual peak count based on the monthly counts recorded from September (of the year indicated) through to March (of the following year). ... : Monthly autumn and winter (September-March) waterfowl counts were collected from land-based vantage points. Counts were conducted by SNH at monthly intervals between 1967 and 1994, and at monthly intervals using the Wetland Bird Survey (WeBS) methods (Austin et al., 2008) since 1995. Since 2003 the surveys have been carried out fortnightly and from 2008 onwards counts are completed by SNH in collaboration with RSPB Loch Leven. There are some gaps in the dataset where monthly counts were not completed. Peak Pink-footed goose counts are dawn roost counts rather than standard WeBS count methods. Validation of data was in line with protocols referenced in the supporting documents. The dataset was quality controlled by Neil Mitchell who has worked at Loch Leven since 2009, and his predecessor SNH Reserve Wardens. ...